Oral communication strategies instruction: Voices from Indonesian English language lecturers - Abid (Curtin University, 2016)
This present study investigated the perspectives of Indonesian English lecturers of oral communication strategies instruction on the English Education Program in the Province of Gorontalo, Indonesia. Data were collected using interviews with lecturers and pre-service teachers majoring in the program, and from teaching syllabuses and classroom observations. Informed by a constructivist paradigm and a thematic analysis approach, the study sought to inform English language lecturers in the English Education Program.